2004
DOI: 10.1002/ajmg.a.30349
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic studies identified a single nucleotide polymorphism in glyoxalase I as autism susceptibility factor

Abstract: Autism is a neurodevelopmental disability characterized by deficits in verbal communications, impairments in social interactions, and repetitive behaviors. Several studies have indicated strong involvement of multigenic components in the etiology of autism. Linkage analyses and candidate gene search approaches so far have not identified any reliable susceptibility genes. We are using a proteomic approach to identify protein abnormalities due to aberrant gene expression in autopsied autism brains. In four of ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(137 citation statements)
references
References 47 publications
7
127
3
Order By: Relevance
“…The present study may also provide mechanistic insight into GLO1's proposed associations with other CNS diseases, such as autism (48,49), affective disorders (50,51), panic disorder (52), and schizophrenia (53). Human genome-wide association studies have identified an association between restless legs syndrome (RLS) and a haplotype containing GLO1 (54,55).…”
Section: Discussionmentioning
confidence: 89%
“…The present study may also provide mechanistic insight into GLO1's proposed associations with other CNS diseases, such as autism (48,49), affective disorders (50,51), panic disorder (52), and schizophrenia (53). Human genome-wide association studies have identified an association between restless legs syndrome (RLS) and a haplotype containing GLO1 (54,55).…”
Section: Discussionmentioning
confidence: 89%
“…43 Several recent studies have demonstrated the power of proteomics in understanding disease processes and elucidating the molecular defects associated with various conditions. 42,[44][45][46][47] Junaid et al 48 recently performed a proteomics study of autopsied brains of individuals with autism and found abnormalities that led to the identification of a single nucleotide polymorphism (SNP) in glyoxalase I, suggesting that it could be a susceptibility factor in autism. 48 The current cross-sectional study was designed to examine the proteome in serum from blood of children with autism (n = 69) ages four to six compared to typically developing children (n = 35) with similar age and gender distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Carriers of the Glyo-1 gene are susceptible to autism, and Glyo-1 variants are associated with autism [171][172]. These studies also found elevated levels of AGE receptors (RAGEs) and an accumulation of AGE the brains of people with autism.…”
Section: Other Rolementioning
confidence: 86%